Comprehensive Analysis of the Transcriptome-Wide m6A Methylome of Heart via MeRIP After Birth: Day 0 vs. Day 7 - Yang, Chuanxi; Zhao, Kun; Zhang, Jing; Wu, Xiaoguang; Sun, Wei; Kong, Xiangqing; Shi, Jing (Frontiers in Cardiovascular Medicine, 2021)
Aim: To systematically classify the profile of the RNA m6A modification landscape of neonatal heart regeneration. Materials and Methods: Cardiomyocyte proliferation markers were detected via immunostaining. The expression of m6A modification regulators was detected using quantitative real-time PCR (qPCR) and Western blotting. Genome-wide profiling of methylation-modified transcripts was conducted with methylation-modified RNA immunoprecipitation sequencing (m6A-RIP-seq) and RNA sequencing (RNA-seq). The Gene Expression Omnibus database (GEO) dataset was used to verify the hub genes. Results: METTL3 and the level of m6A modification in total RNA was lower in P7 rat hearts than in P0 ones. In all, 1637 methylation peaks were differentially expressed using m6A-RIP-seq, with 84 upregulated and 1553 downregulated. Furthermore, conjoint analyses of m6A-RIP-seq, RNA-seq, and GEO data generated eight potential hub genes with differentially expressed hypermethylated or hypomethylated m6A levels. Conclusion: Our data provided novel information on m6A modification changes between Day 0 and Day 7 cardiomyocytes, which identified that increased METTL3 expression may enhance the proliferative capacity of neonatal cardiomyocytes, providing a theoretical basis for future clinical studies on the direct regulation of m6A in the proliferative capacity of cardiomyocytes.